QRIS sebagai Instrumen Kedaulatan Ekonomi Digital: Analisis Protes Amerika Serikat terhadap Sistem Pembayaran Indonesia - Achmad Amzal Maulana; Ampauleng; Salma Abdullah; Siti Fatimah (LPPM STIEM BONGAYA, 2026)
QRIS (Quick Response Code Indonesian Standard) is a strategic policy issued by Bank Indonesia to standardize the national digital payment system. This study aims to analyze the urgency of QRIS as an instrument of digital economic sovereignty and the dynamics of the United States' protest against this policy. Using a qualitative approach with a multiple case study method, this research analyzes Bank Indonesia policy documents, the 2024 USTR report, and related literature. The results show that QRIS improves transaction efficiency, financial inclusion, and state oversight of domestic money flows. However, data localization and national standardization policies triggered a US protest through the USTR, which considered them trade barriers. Indonesia responded with coalition diplomacy through the ASEAN Digital Economy Framework Agreement (DEFA) and strengthened sovereignty-based digital governance. This study concludes that QRIS functions not only as a payment tool but also as a strategic instrument of digital economic sovereignty amid global competition. Policy recommendations include strengthening regulations, improving digital literacy, and fostering South-South collaboration to reduce dependence on foreign payment systems.